Artificial Intelligence, Social Media, and Modern Teenagers - Hikmawati, Hanifah; Darma, Mega Putri Aulia (INCARE, International Journal of Educational Resources, 2025)
AI is known as artificial intelligence as a computer system-based technology that has the ability to carry out human activities. Its reliable intelligence in storing data or "remembering knowledge" in large amounts, as well as its ability to transfer this intelligence in any condition and anywhere at high speed, is the reason why its existence is very popular with humans, especially teenagers/young people. To support the running of this AI system, many teenagers first explore social media as an intermediary for them in surfing insights through social media. The method used in this research is a qualitative approach method where researchers take literature study methods sourced from journals, theses, the internet and others and then analyze them according to the predetermined problem topics. The use of artificial intelligence in smart content makes it easier to search, group and find digital materials and books that have been programmed virtually more quickly and efficiently. Examples of the use of this technology can be found in various digital libraries, both in schools, universities and public libraries. Artificial intelligence can help in finding and categorizing the books needed quickly and in an organized manner. There are many influences that arise for teenagers in using AI and social media, it is necessary to take strategic steps to prevent negative impacts or influences on teenagers, namely providing education for teenagers in their developmental transition from school or parents. The provision of facilities to teenagers needs to be adjusted to their needs and there must be continuous monitoring of things that teenagers do. There is also a need for understanding from a psychological, cognitive and social-emotional perspective for parents and educators so that they can respond quickly if something might happen during use. Social media AI. AI and social media for today's teenagers are more about keeping up with the times, the benefits they get lead to their existence in this regard, regardless of what influence their use causes, such as the influence on teenage psychology.